Prognostic value of epicardial adipose tissue in heart failure: a systematic review and meta-analysis - Wu, Qingqun; Guo, Junhan; Liu, Fengru; Dong, Chenchen; Wang, Yu; Liu, Lu; Zhang, Shulong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEpicardial adipose tissue (EAT) essentially affects the pathophysiologic development of heart failure (HF), while existing research has not well elucidated its prognostic value for outcome. The present study aims at including relevant studies for systematically assessing its prognostic value in HF patients.MethodsThe studies assessing the way EAT was employed to predict adverse HF outcomes were included from PubMed, Web of Science, Embase, and the Cochrane Library databases, and relevant data were accurately extracted. The primary outcome included the composite outcome of HF hospitalization and all-cause mortality (ACM). Secondary outcomes were the composite outcome of cardiovascular death and HF hospitalization and HF rehospitalization. We combined the standard mean difference (SMD) of EAT in HF patients with and without adverse events (AEs) and the EAT to adverse outcome hazard ratio (HR).ResultsThe nine included studies involved 1,939 HF patients and 329 control populations. HF patients with AEs presented a higher EAT vs. those without (SMD: 3.33, CI: 0.96–5.69, p = 0.006, I2 = 98%). Increased EAT per unit indicated a higher risk of the composite outcome of HF hospitalization and all-cause mortality (HR: 1.28, CI: 1.42–1.85, p = 0.0002, I2 = 93%) and HF readmission (HR: 1.05, CI: 1.03–1.07, p < 0.001, I2 = 10%), but did not relate to that of cardiovascular death and HF hospitalization (HR: 1.17, CI: 0.99–1.39, p = 0.06, I2 = 76%). The pooled AUC value for EAT to predict the primary outcome was 0.74 (CI: 0.66–0.82, p = 0.018, I2 = 70.1%) in HF patients with EF >40%.ConclusionEAT is considered a clinical predictor of the composite outcome of HF hospitalization and ACM and may contribute to the prediction of poor prognosis in HF patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/, identifier [CRD420250653252].